Baseline for cocoa cultivation in Antioquia (Colombia): methodology, attributes, and implementation - Flórez Ramos, Vanessa Lucia; Marín Tangarife , Carlos Alejandro; Mejía Córdoba, Carlos Arturo; Velasquez Velez, Maria Isabel (Revista Colombiana de Investigaciones Agroindustriales, 2022)
Considering the development of agricultural products in the department of Antioquia, there is a need to determine a baseline that allows centralizing information and having a starting point to compare and determine the advances and setbacks in relation to specific products. A baseline study seeks to know the initial situation of the population with respect to the development of a project. In this work, the attributes and methodologies are defined for the implementation of a baseline for cocoa producers (Theobroma cacao L.) of 5 subregions of Antioquia, Colombia (Magdalena Middle-Northeast, Southwest, Urabá, West, Low Cauca). This includes the definition of the basic attributes for the implementation of a baseline that contains a location (georeferencing), producer data, family nucleus, crop data, and connectivity; each dimension (variable) is given coding (attribute and type of information), operational definition, unit of measurement, category, scale of measurement, data collection, and indicators. It is confirmed that the characterization of the baseline for cocoa producers through the proposed methodology allows versatility at the time of data collection in the field. However, the use of digital tools allows a better centralization of information and territorial targeting.